THE EFFECTIVENESS OF MONETARY POLICY IN DEALING WITH ECONOMIC CRISIS: A LITERATURE REVIEW - H. Mohdari; Selvanus; Ec. Lydia Goenadhi (CV. Adiba Aisha Amira, 2024)
Economic crises force policymakers to employ various monetary policy instruments in order to lessen the effects. In this research paper, literature research method is utilized. Results demonstrate how monetary policy (in the form of interest rate cuts, quantitative easing and open market operations) has been utilized to increase liquidity in markets, stabilize the financial system and support economic growth even during periods of recession. Monetary policy success relies upon its swift implementation, relevant measures, and economic conditions prevailing at that moment. While non- traditional monetary policies adopted during the economic crisis have had positive results, they also come with risks and side effects including potential long-term inflation and asset bubble formation. Therefore, conclusions draw indicate the need for closer coordination between monetary and fiscal policies as well as adaption of a sustainable approach for meeting future challenges to economic health.